2005
DOI: 10.1063/1.1897047
|View full text |Cite
|
Sign up to set email alerts
|

Strain relaxation of epitaxial SrTiO3 thin films on LaAlO3 by two-step growth technique

Abstract: Using pulsed-laser deposition, a two-step growth technique was applied to epitaxial SrTiO3 (STO) thin films on LaAlO3 substrates providing a way to obtain an effective strain relaxation in these films otherwise strained due to lattice mismatch between film and substrate. By changing the thickness of a first layer, deposited at a temperature as low as 100°C before the deposition of the main layer at 750°C, different strain relaxation states of the films could be systematically realized. With a 10-nm-thick first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 21 publications
2
35
0
Order By: Relevance
“…We noted a higher density of defects in the film's lower part than in its upper part; evidently, strain was relaxed there, consistent with our previous reports. 8,9 In addition, in Figs. 1(c) and 1(d), we observed moiré fringes at the interface because of the overlapping of film and substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We noted a higher density of defects in the film's lower part than in its upper part; evidently, strain was relaxed there, consistent with our previous reports. 8,9 In addition, in Figs. 1(c) and 1(d), we observed moiré fringes at the interface because of the overlapping of film and substrate.…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrated an effective reduction in strain in epitaxial STO thin films on a LaAlO 3 (LAO) substrate using pulsed laser deposition (PLD). 8,9 We found that a 10-nm first layer (FL) can almost completely relax the strain induced by lattice mismatch between the film and its substrate. The two-step-grown STO film exhibited substantially higher permittivity and tunability than the conventional films grown by a single-step process, which were under compressive strain.…”
Section: Introductionmentioning
confidence: 99%
“…Results and discussion 3.1 BST films directly deposited on c-Al 2 O 3 Figure 2 shows the XRD ª2ª patterns of BST films directly deposited on c-Al 2 O 3 at different oxygen pressures. The BST film deposited at 13 Pa (that is in the typical pressure range for BST depositions 8),9), 12) ) showed the polycrystalline nature. In addition, the film deposited at lower oxygen pressure of 7 © 10 ¹2 Pa was also polycrystalline, although the orientation ratio was slightly different.…”
Section: Methodsmentioning
confidence: 99%
“…Each application imposes different requirements for the dielectric materials, among which the most desired properties are large tunability combined with a low microwave loss. The polycrystalline dielectric thin films often show lower permittivity as compared to the bulk whereas high quality epitaxial films can have a permittivity close to that of single crystal [1,5,6]. Interfacing dielectric oxides with semiconductors will allow us to take advantage of such material properties for multifunctional devices.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric-semiconductor heterostructures are of great interest for electronic and optoelectronic applications ranging from communication devices to satellite services [1][2][3][4]. Each application imposes different requirements for the dielectric materials, among which the most desired properties are large tunability combined with a low microwave loss.…”
Section: Introductionmentioning
confidence: 99%